Analysis of the Physicochemical Properties of Acaricides Based on Lipinski's Rule of Five - Chen, Xiaoxia; Li, Hao; Tian, Lichao; Li, Qinwei; Luo, Jinxiang; Zhang, Yongqiang (Journal of computational biology, 2020)
This study aimed to explore the similarity between the physical and chemical properties of different acaricides, determine whether Lipinski's Rule of Five (RO5) used in the design of drug molecules is suitable for screening acaricides, and provide methods for selection of new acaricides. We evaluated and predicted the molecular properties of >180 acaricides using Molinspiration. We calculated physicochemical property parameters, such as log , molecular weight (MW), and number of hydrogen bond donors (HBDs), hydrogen bond acceptors (HBAs), and rotatable bonds (Rot B). We then conducted qualitative and quantitative analyses of the physicochemical properties of acaricides. The MW of all acaricides ranged from 141 to 663, with an average value of 337.8. The number of HBDs ranged from 0 to 5, with an average value of 0.46. The number of HBAs ranged from 0 to 9, with an average value of 4.07. The log ranged from -0.79 to 8.74, with an average value of 4.61. The number of Rot B ranged from 0 to 14, with an average value of 5.62. Except for the microbial and plant-derived acaricides, the molecular properties of the remaining acaricides are in accordance with the Lipinski's RO5. Therefore, the Lipinski's RO5 can provide a basis for screening new acaricide drugs.